Stability analysis of leishmania epidemic model with harmonic mean type incidence rate - Khan, Amir; Zarin, Rahat; İnç, Mustafa; Zaman, Gul; Almohsen, Bandar (Springer Heidelberg, 2020)
We discussed anthroponotic cutaneous leishmania transmission in this article, due to its large effect on the community in the recent years. The mathematical model is developed for anthroponotic cutaneous leishmania transmission, and its qualitative behavior is taken under consideration. The threshold number R0 of the model is derived using the next-generation method. In the disease-free case, local and global stability is carried out with the condition that R0 will be less than one. The global stability at the disease-free equilibrium point has been derived by utilizing the Castillo-Chavez method. On the other hand, at the endemic equilibrium point, the local and global stability holds with some conditions, and R0 is greater than unity. The global stability at the endemic equilibrium point is established with the help of a geometrical approach which is the generalization of Lyapunov theory, by using the third additive compound matrix. The sensitivity analysis of the threshold number with other parameters is also taken into account. Several graphs of important parameters are discussed in the last section.
Keywords: Anthroponotic Cutaneous Leishmaniasis; Threshold; Sandflies; Virus; Hosts